Executive compensation and firm performance: Evidence from Nepalese commercial banks (The Lumbini Journal of Business and Economics, 2023)
NRB provision to relate executive’s fixed annual compensation with staff salary and total assets of the respective Banks is different from those of other country (Bhatta, 2010). This is the first study to examine the relationship between executive compensation and firm performance in Nepalese banking industry. Data are collected from 21 commercial banks from the study period 2014/15 to 2020/ 21. Panel data are analyzed through pooled OLS and fixed effect model by using three control variables (i.e. Leverage, size and risk). Result showed that executive compensation is not influenced by firms performance in Nepalese commercial banks. Result also revealed that pay performance relationship is not influenced by size of the firms. It is concluded that possible reason for this insignificant relationship is contradict and impractical compensation directives issued by NRB, as claimed by (Bhatta,2010)